Association of stress-related disorders with subsequent risk of all-cause and cause-specific mortality: A population-based and sibling-controlled cohort study - Fan Tian; Qing Shen; Yihan Hu; Weimin Ye; Unnur A. Valdimarsdóttir; Huan Song; Fang Fang (Elsevier, 2022)
Summary: Background: Prior research provides suggestive evidence on an association between stress-related disorders and mortality. No previous study has however addressed the role of familial confounding on such association. Methods: We conducted a nationwide cohort study of 189,757 individuals with a first-onset stress-related disorder between January 1, 1981 and December 31, 2016 in Sweden (i.e., exposed patients), 1,896,352 matched unexposed individuals, and 207,479 unaffected full siblings of the exposed patients. Cox proportional hazards models were used to estimate the hazard ratios (HRs) and 95% confidence intervals (CIs) of all-cause and cause-specific mortality. Findings: During a mean follow-up of 9.42 years, an elevated risk of all-cause mortality was observed during the entire follow-up among patients with stress-related disorders, compared with either unexposed individuals or their unaffected full siblings. Such excess risk was most pronounced within the first year after diagnosis of stress-related disorders (HR, 3.19 [95% CI, 2.87-3.54] in population-based comparison; HR, 3.21 [95% CI, 2.56-4.02] in sibling-based comparison). The excess risk decreased but remained statistically significant thereafter (HR, 1.64 [95% CI, 1.60-1.67] in population-based comparison; HR, 1.61 [95% CI, 1.54-1.68] in sibling-based comparison). An increased risk was observed for almost all cause-specific mortality, with greater risk increase for deaths from unnatural causes, especially suicide, and potentially avoidable causes. Interpretation: Stress-related disorders were associated with an increased risk of all-cause mortality and multiple cause-specific mortality, and the risk elevation was independent of familial confounding. The excess mortality attributable to unnatural causes and potentially avoidable causes highlights the importance of clinical surveillance of major health hazards among patients with stress-related disorders. Funding: EU Horizon 2020 Research and Innovation Action Grant, 1.3.5 Project for Disciplines of Excellence at West China Hospital of Sichuan University, National Natural Science Foundation of China, Icelandic Research Fund (Grant of Excellence), ERC Consolidator Grant, and Swedish Research Council.